A generic algorithm for sequential, rectangular, space filling layouts - Baudel, Thomas; Broeksema, Bertjan (InfoVis'11: Poster at the IEEE Conference on Information Visualization, 2011)
We present a generic algorithm to sequentially pave a rectangular area with smaller, fixed-surface, rectangles. The parameters of this algorithm are functional, and it covers the full design space considered. This class of layouts is interesting, because it includes all kinds of treemaps involving the placement of rectangles. For instance, Slice and dice, Squarified, Strip and Pivot layouts are obtained through various formulations of two simple chunking and phrasing functions. Some new and potentially interesting layouts which can be generated using our algorithm are introduced, such as spiral treemaps and data dependent variations of known layout strategies.